2012
DOI: 10.1016/j.neurobiolaging.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, neural atrophy, and the effect of caloric restriction in rhesus monkeys

Abstract: Higher serum homocysteine (Hcy) levels in humans are associated with vascular pathology and greater risk for dementia, as well as lower global and regional volumes in frontal lobe and hippocampus. Calorie restriction (CR) in rhesus monkeys (Macaca mulatta) may confer neural protection against age- or Hcy-related vascular pathology. Hcy was collected proximal to an MRI acquisition in aged rhesus monkeys and regressed against volumetric and diffusion tensor imaging indices using voxel-wise analyses. Higher Hcy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 61 publications
(70 reference statements)
1
17
0
Order By: Relevance
“…The interaction between age and CR in prior reports implicated gray matter in the mid-cingulate cortex and small clusters in the thalamic bundle and superior longitudinal fasciculus for FA and MD. For other age-related biomarkers of interest, such as homocysteine (Willette et al 2012a), the interaction with dietary condition revealed a shallower slope of association with gray matter in the right hippocampus. A similar association with hippocampal gray matter was found in the current analyses of IL-8.…”
Section: Discussionmentioning
confidence: 96%
“…The interaction between age and CR in prior reports implicated gray matter in the mid-cingulate cortex and small clusters in the thalamic bundle and superior longitudinal fasciculus for FA and MD. For other age-related biomarkers of interest, such as homocysteine (Willette et al 2012a), the interaction with dietary condition revealed a shallower slope of association with gray matter in the right hippocampus. A similar association with hippocampal gray matter was found in the current analyses of IL-8.…”
Section: Discussionmentioning
confidence: 96%
“…In addition CR monkeys showed less WM atrophy and more microstructural density per point higher homocysteine levels primarily in brainstem and cerebellum, as well as less GM atrophy in occipital, hippocampal, caudoputamen, and anterior cingulate areas (Willette et al, 2012b). CR also considerably reduced stress reactivity (Willette et al, 2012c), where aged monkeys on CR showed less corresponding atrophy per point increase in a z-scored stress factor in many WM tracts, as well as similar amelioration in GM volume or microstructural density for orbital PFC and hippocampus.…”
Section: 0 Discussionmentioning
confidence: 99%
“…This new cortical mapping study complements prior studies associating high levels of homocysteine with overall brain volume reduction, WM atrophy rate, baseline volume and atrophy rate of the hippocampus and medial temporal lobe (Clarke et al, 1998a, den Heijer et al, 2003, Douaud et al, 2013, Firbank et al, 2010, Williams et al, 2002), lower tissue volumes in frontal and parietal WM (Rajagopalan et al, 2011), greater cortical atrophy (den Heijer et al, 2003), longitudinal ventricular volume enlargement in elderly individuals with arteriosclerotic disease (Jochemsen et al, 2012), lower whole brain GM volume in non-demented elderly (Whalley et al, 2003) in humans and with lower GM volume and density in prefrontal cortices and striatum in rhesus monkeys (Willette et al, 2012). Our prior study in an almost entirely overlapping subject population – but with a different method, TBM – found WM tissue contraction (Rajagopalan et al, 2011) in areas that structurally connect the GM regions we see here in the cortex.…”
Section: Discussionmentioning
confidence: 99%